Inflation and Economic Growth Nexus in BRICS: Evidence from ARDL Bound Testing Approach - Behera, Jaganath; Mishra, Alok Kumar (Asian Journal of Economic Modelling, 2015)
The present study investigated the inflation growth nexus in the context of BRICS countries. The study used time series data covering from the period 1980 to 2012. The data sources are cumulated from the World Bank, World Economic Outlook (WEO). The empirical findings of the study indicate that a long run positive relationship between inflation and economic growth only for China and South Africa at the 5 percent level of significance. The study also found that there is a unidirectional causality between economic growth and inflation in the context of India whereas; bidirectional causality takes place in the case of China. The VAR analysis could not find a consistent short run relationship between inflation and economic growth over ten years ahead for BRICS countries. From the policy implication point of view the study suggests that policy makers in BRICS should consider the short run relationship between inflation and economic growth while, the China and South Africa policy makers should pay attention to both short run and long run relationship.